UJI AKTIVITAS ANTIOKSIDAN EKSTRAK BUAH PURNAJIWA (Kopsia arborea Blume.) DENGAN BERBAGAI PELARUT - Didit Purwanto; Syaiful Bahri; Ahmad Ridhay (KOVALEN: Jurnal Riset Kimia, 2017)
Antioxidant activity of Purnajiwa (Kopsia arborea Blume.) fruit has been investigated.The fruit was extracted by various solvents such as n-hexane, ethyl acetate, and ethanol. The aim of the research is to define a class of compounds and antioxidant activity. The compounds test was conducted by the phytochemical method. The results showed that the purnajiwa fruit extract is classified as secondary metabolites of flavonoids, saponins, tannins, alkaloids, and steroids. The antioxidant activity was tested by DPPH method and the amount of antioxidant activity was characterized by IC50 values. The result indicated that the antioxidant activity (IC50) for n-hexane, ethyl acetate, and ethanol solvents is 3524.05 ppm, 316.09 ppm, and 154.89 ppm respectively.Keywords: Purnajiwa Fruit, Antioxidant, DPPH, Phytochemicals